Influence of Village Funds and Policies on Community Welfare: A Brief Overview - Fadilah, Elmi Nur; Biduri, Sarwendah (Indonesian Journal of Public Policy Review, 2024)
This research investigates the influence of village funds, allocation strategies, policies, and institutional frameworks on community welfare and accountability in village fund management. Utilizing a quantitative approach, a sample of 54 respondents from villages surrounding the Pandaan sub-district was selected using purposive sampling techniques. Data was collected through Google Forms and analyzed using the SmartPLS program, employing both inner and outer model analyses. The findings indicate significant positive effects of village fund variables, allocation strategies, and policies on community welfare. However, village institutional variables were found to have no significant impact on community welfare. These results underscore the importance of effective management strategies and policies in ensuring the welfare of communities in rural settings, thereby informing policymakers and stakeholders involved in local governance and development. Highlights : The study examines the influence of village fund management on community welfare in rural settings. Findings highlight the significance of allocation strategies and policies in enhancing community welfare. Implications underscore the importance of effective management practices for rural development and governance. Keywords: Village funds, Community welfare, Accountability, Rural development, Quantitative study